Dynamic skin: Interacting with space: An inter-media interface between people and space - Chang, T.; Jiang, H.; Chen, S.; Datta, Sambit (School of Architecture Hindustan University, 2012)
Space in its physical form provides the major architectural experience for the people inside the space. How people interact with their surrounding space dynamically is a noteworthy research topic. Architectural skin (or "skin" in this project) is the physical interface between people and their surroundings. The skin in this sense represents an inter-media that receive/sense the interactive behaviours of people and react back into space. Further, the skin needs to be mediated and reacted dynamically according to the interaction behaviours. With the case studies, the knowledge of skin design has achieved the feasibility of skin design for dynamic skins, the multiple channels of input sensors are desired. Thus, a system called dynamic skin is proposed and details of process are evaluated. In order to incorporate the diverse scenario appeared in the cases and prototypes, a distributed system approach such as multi-agent system design is appealing to us. We propose a distributed dynamic skin platform that cannot only provide sufficient interaction between people and space, but also extending such space to the cloud and network.